(untitled) (La U Investiga, 2022)
Metabolic syndrome, a chronic and progressive pathophysiological state, represents a group of risk factors that, if identified early, have an impact on morbidity and mortality in the exposed population. An observational, descriptive and cross-sectional study was carried out, with the objective of identifying risk factors related to metabolic syndrome in workers of the Fire Department of the city of Ibarra, during the period 2021 - 2022. They were selected according to work characteristics and previous health conditions. , carried out through non-probabilistic, intentional by criteria. The data was obtained from the payroll and access to established periodic medical check-ups, and the ATP III scale was applied in its modified version for Latin America to establish the risk diagnosis of Metabolic Syndrome, as well as those with the work environment according to the scale of Likert, results that were reflected in tables with frequency analysis and statistical significance considered when p ≤0.05. Young adults prevail, 42.35%, the predominant male sex with 68.23%, the workers with 78.23%. Twenty cases of metabolic syndrome were found, 11.8%. Abdominal obesity prevails with 21.76%, hyperlipidemia with 52.35%, hyperglycemia, 6.47% and arterial hypertension with 2.94%. In the study group, other risk factors for metabolic syndrome related to the work environment were found, with limited communication, poor nutrition, rest and self-care of health in general predominating significantly in men. Women, regardless of occupation, are the ones who most often do not practice physical exercises.